Sex Education: Fact or Fiction? - Doreen MacIntosh (AOSIS, 1985)
The words Sex and Sexuality when coupled with the word Love should make a most exciting phrase. Sexual love is a source of power that makes life worth living. We seek each other out for comfort, pleasure, companionship, intellectual compatibility, inspiration and more importantly, our powerful sexual drives ensures the existence of mankind through reproduction. Human sexuality has the potential to provide us with an important source of goodness in our lives. It rewards us to know as much as we can about it and how to make it work positively for us and our children.